Transforming Home Appliances into IoT Devices - Freire, João Emanuel Araújo (2019)
Home appliances were, until not very recently, isolated devices uncapable of communicate with others. With the recent technological advances is it possible nowadays to connect all these devices to the internet enabling them with the capacity to communicate between them and also the possibility to store and analyse the data generated making them more efficient. Due to these advancements, terms like Internet of Things and Cloud Computing surfaced. These terms represent architectures that allow communications and interactions between devices. The potential of these technologies is substantial for the improvement of productivity and eco-nomic impact. These advancements allowed home appliances to generate an enormous amount of data, and as repercussion, the need for structures able to receive, storage and process the data emerged. The present document contains a proposition of an architecture that allows to collect and send home appliances’ data to the Cloud, a way to store and make them available to other applications and a platform that allows the data’s visualisation and analysis. The proposed architecture was tested with a refrigerator offered by Electrolux inserted in the ProSEcO project.